The effect of crowd support on home-field advantage: Evidence from European football - Inan, T. (Annals of Applied Sport Science, 2021)
Background. Home field advantage exists in all professional games including professional football. Studies have revealed persistent home advantage across countries and divisions. Although crowd effects have regularly been cited as one of the potential causes of home advantage, the effect of crowd size and crowd density on home advantage has not been demonstrated in any football league. Objectives. The aim of this study was to demonstrate this effect using a new theoretical framework and binary logistic regression. Methods. Data collected for four seasons of five major European Leagues was processed. For this reason, 4 seasons and n = 8530 matches were analyzed starting from 2015 to 2019. Results. The model results suggest the presence of home-field advantage for all major European Leagues with varying degrees and varying shares attributable to the crowd support and crowd density. Conclusion. In the present study, it was found that crowd support and crowd density are of great importance for home-field advantage. The results of the model used in this study suggest that there is a statistically significant level of home-field advantage for all major European leagues. According to the results, the share of home-field advantage attributable to crowd support differs dramatically among divisions and for Serie A and Bundesliga crowd support does not even have any statistical effect on points earned at home. These results show us that binary regression analysis can be used to determine the crowd effect in leagues with an average occupancy rate of 70% in football leagues. In the present study, It has been determined that crowd support and crowd density are important variables that contribute to the home-field advantage in football.